Efektivitas Latihan Dual Task Terhadap Keseimbangan dan Fungsi Kognitif Lansia dengan Risiko Jatuh di Balai Pelayanan Sosial Tresna Werdha Yogyakarta dan Wisma Jolotundo - Muhammad Farras Al Fatih; Arif Widodo (Jurnal Ners, 2026)
Introduction: Older adults are a vulnerable age group that often experiences a decline in cognitive function and balance, which may increase the risk of falls. This decline is associated with physiological changes in the nervous and musculoskeletal systems as part of the aging process. One non-pharmacological intervention that can be implemented is dual task training, which combines motor and cognitive activities performed simultaneously. Objective: To determine the effectiveness of dual task training on cognitive function and balance among older adults at risk of falls at the Balai Pelayanan Sosial Tresna Werdha Yogyakarta and Wisma Jolotundo. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 9 older adults selected using purposive sampling. The intervention in the form of dual task training was conducted for 2 weeks with a frequency of 2–3 sessions per week. Cognitive function was measured using the Mini Mental State Examination (MMSE), while balance was assessed using the Timed Up and Go (TUG) test. Data were analyzed using univariate and bivariate analyses with the Wilcoxon test. Results: The average MMSE score increased from 22.67 at the first session to 25.44 at the third session. In addition, the average TUG time decreased from 18.33 seconds to 14.33 seconds. Statistical test results showed a significance value of p = 0.008 (p < 0.05), indicating a significant difference before and after the intervention. Conclusion: Dual task training was effective in improving cognitive function, as measured by the MMSE questionnaire, and balance, as measured by the TUG test, as well as reducing the risk of falls among older adults at the Balai Pelayanan Sosial Tresna Werdha Yogyakarta and Wisma Jolotundo.